1977
DOI: 10.1021/jm00220a025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-benzyloxy and 2-benzylthio analogs of primaquine as potential antimalarials

Abstract: A series of 2-benzyloxy and 2-benzylthio analogues of primaquine has been synthesized and evaluated against Plasmodium berghei in the mouse and Plasmodium cynomolgi in the rhesus monkey. 8-Aminoquinoline toxicity, as measured in the Rane mouse screen, was reduced, and these compounds showed significant blood schizonticidal antimalarial activity in mice. In monkeys, significant tissue-schizonticidal activity was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Recovery studies we carried out have shown that 5-hydroxyprimaquine and its oxidized products irreversibly bound to proteins (or other macromolecules), with resulting very low recovery. Of other ring-hydroxylated metabolites which are capable of undergoing redox cycling, 7-hydroxy-primaquine is also expected to be unstable, whereas synthetic 2-and 4-hydroxyprimaquine were found to be stable (37,38). Even though ringhydroxylated primaquines have been shown to cause hematotoxicity in vitro, their relative distribution in the liver and erythrocytes has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery studies we carried out have shown that 5-hydroxyprimaquine and its oxidized products irreversibly bound to proteins (or other macromolecules), with resulting very low recovery. Of other ring-hydroxylated metabolites which are capable of undergoing redox cycling, 7-hydroxy-primaquine is also expected to be unstable, whereas synthetic 2-and 4-hydroxyprimaquine were found to be stable (37,38). Even though ringhydroxylated primaquines have been shown to cause hematotoxicity in vitro, their relative distribution in the liver and erythrocytes has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…In an initial clinical trial (Ethiopia, 1970), primaquine displayed minor efficacy (1 patient of 7 patients was cured) against diffuse CL [88]. However, an observation that the 2-benzyloxy derivative of primaquine was less toxic [89,90], and toxicity were considered in some of these studies [97,99,101,102]. These delivery systems were aimed at increased effectiveness, prolonged duration of action and / or reduced toxicity of the drug.…”
Section: Primaquinementioning
confidence: 99%
“…Since resistance to the 8-aminoquinolines does not appear to be a problem, numerous efforts to create new PrimQ-analogues with improved potential prophylactic action and/or less toxic [167,168]. Now two promising antimalarial agents, 2-tert-butylprimaquine (64) and tafenoquine (65), are available.…”
Section: Design Of Novel Primq Hybridsmentioning
confidence: 99%